Preliminary Phytochemical Screening of wild edible fruits from Boda and Kolli hills - Anand, S.P.; Deborah, S. (Journal of Medicinal Herbs and Ethnomedicine, 2017)
Medicinal plant plays a vital role for ailment of various chronic diseases due to the presence of phytochemical constituent. The preliminary phytochemical compounds was studied by using the ethanol, ethyl acetate, diethyl ether, chloroform and aqueous extracts of 15 wild edible fruits collected from Boda and Kolli Hills. The phytochemical compounds such as Phenol, tannins, saponin, alkaloid, flavonoids, steroids, phlobotannins, terpenoids, anthroquinones and cardiac glycosides were screened in 15 edible fruits by using standard methods. The diethyl ether extract, ethyl acetate and ethanol extract of the selected fruits shows the presence of phytochemicals compound. The highest occurrence shows the high therapeutic value possessing majority of phytochemical constituent of active compounds. In Further studies, the compound from these fruits were isolated and used for medicinal purposes